2020
DOI: 10.21203/rs.3.rs-56548/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Musculoskeletal Pain, Fatigue and Grip Strength in Hospitalized Patients with COVID-19

Abstract: IMPORTANCE Coronavirus disease 2019 (COVID-19) is an emerging disease that was declared as a pandemic by WHO. Although there are many retrospective studies to present clinical aspects of the COVID-19, still the involvement of the musculoskeletal system has not been deeply investigated.OBJECTIVE To classify the symptoms of musculoskeletal system in COVID-19 patients, to evaluate myalgia, arthralgia and physical/mental fatigue, to assess handgrip muscle strength, and to examine the relationship of these paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…19 Another study recruiting 150 hospitalized COVID-19 patients (mean age of 53 years) compared the musculoskeletal findings (including grip strength) and revealed that female (but not male) patients with severe COVID-19 disease had lower grip strength as compared to nonsevere ones. 20 In our relatively larger study (N=312) with younger subjects (mean age of 46 years), we found that low grip strength independently increased (about three times) the risk of severe disease course in COVID-19.…”
Section: Discussionmentioning
confidence: 61%
“…19 Another study recruiting 150 hospitalized COVID-19 patients (mean age of 53 years) compared the musculoskeletal findings (including grip strength) and revealed that female (but not male) patients with severe COVID-19 disease had lower grip strength as compared to nonsevere ones. 20 In our relatively larger study (N=312) with younger subjects (mean age of 46 years), we found that low grip strength independently increased (about three times) the risk of severe disease course in COVID-19.…”
Section: Discussionmentioning
confidence: 61%
“…This study shows that muscle strength is independently associated with the risk of severe COVID-19 in adults 50 years of age or older. These findings further highlight muscle strength as an important factor to monitor in COVID-19 patients (19, 34, 38), thereby suggesting that hand-grip strength could improve the accuracy of composite scores used to predict COVID-19 severity (19, 39, 40).…”
Section: Discussionmentioning
confidence: 62%
“…For patients with neurological sequelae from COVID-19, rehabilitation (both appropriate assessments and programs) will also be critical in their recovery, especially in patients who were admitted to the intensive care unit. ( Curci et al, 2021 ; de Sire et al, 2021 ; Tuzun et al, 2021 ) Many COVID-19 patients experience fatigue( de Sire et al, 2021 ; Carfì et al, 2020 ) including in the post-acute/chronic phase, and intensive rehabilitation has been shown to improve outcomes. ( Curci et al, 2021 ; Ferraro et al, 2021 )…”
Section: Discussionmentioning
confidence: 99%